El Niño Southern Oscillation (ENSO), Indian Ocean Dipole (IOD), and the Rise of Extreme Temperatures in Eastern Sumatra: Exploring Climate Change Dynamics - Hamdi Akhsan; Muhammad Irfan; Iskhaq Iskandar (Postgraduate, University of Mataram, 2023)
The Indonesian region is affected by the monsoon system, which leads to a rainy season in December-March and a dry season in June-September. Global warming caused by human activities is increasing the risk of extreme climate events like floods, droughts, etc. The study aims to analyze the trends and correlations of extreme temperatures in the South Sumatra coastal area and its relationship with the DMI and Nino 3.4 indices. The four-stage research methodology includes data collection, extreme temperature index calculation, trend detection and correlation analysis with ENSO. Results indicate that the region has seen a rise in temperature, with hot day/night temperatures increasing by 0.26-0.29°C per decade and cold day/night temperatures by 2-3°C per 100-1000 years. A strong correlation was found between the DMI index and daily maximum/minimum temperatures, as well as between the Nino 3.4 index and the Diurnal Temperature Range (DTR). The study projects that nighttime temperatures will increase faster than daytime temperatures in the future, with a proportional correlation between the Nino 3.4 index and extreme temperatures